Pengaruh Penerapan Pemasaran Digital terhadap Pendapatan pada Usaha Mikro Kuliner di Kecamatan Kuantan Mudik - Engla Listia; Fenny Trisnawati; Hardisem Syabrus (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the effect of digital marketing implementation on revenue of culinary micro-enterprises in Kuantan Mudik District. The method used in this study is a quantitative approach with a causal research type. The population in this study were all culinary micro-enterprises that use digital marketing, with a sample of 51 respondents taken using saturated sampling techniques. Data collection was carried out through questionnaires that had been tested for validity and reliability, then analyzed using descriptive analysis and simple linear regression. The results of the study indicate that digital marketing has a positive and significant effect on the revenue of culinary micro-enterprises in Kuantan Mudik District. The coefficient of determination (R2) value of 0.148 indicates that digital marketing is able to explain 14.8% of the variation in revenue, while the rest is influenced by other factors outside the study. The regression equation obtained is Y = 10.018 + 0.070X, which means that every increase in one unit of digital marketing will increase revenue by 0.070 units. The conclusion of this study is that the more optimal the implementation of digital marketing, the greater the opportunity to increase revenue for culinary micro-enterprises.